Isfahan Dental Student's Knowledge and Attituale about Research - M - Ghafournia; Sh Motamedi; E Yousefian (Isfahan University of Medical Sciences, 2006)
Introduction: Scientific development is essential for each type of development. The first step for planning is to know present situation. For planning to improve student role in research, we must know how much do they know about research methodology and what kind of attitude they have about it. The aim of this study was to determine Isfahan dental students' knowledge and attitude about research.Methods and Materials: All Isfahan dental school students (calss of 1999-2003) participated in this cross-sectional descriptive-qualitative study (n=300). Data was collected by self-administered questionnaire consisting of three parts: knowledge, attitude and demographic questions. The content validity of question-naire was confirmed by experts and its reliability by split half method. The face validity was also checked. The data were analyzed by SPSS-11 soft ware using frequency distribution and mean and correlation coefficient list.Result: The mean mark of students' knowledge was 2.09±1.92 out of 10. Which would be increased with inereasing level of training and education. Ninty four persent of students would absulotely agree with necessity of participation in research activity during heir study period, 23.5 percent by increasing quality of services to the patient, 25.4 persent by increasing quality of study skills, 46.3 percent were in agreement with university support for research activity and only 15.1 percent of students believed that participating in research activity is wast of time.Conclusion: According to the results of this study, student's research knowledge is very low in spite of their attendance in research methodology workshops (40.5 persent). Because of their desire and positive attitude toward research activity, faculty officials should plan in more diciplined way, to improve the students' skills and knowledge.Key words: Knowledge, Attitude, Research, Dental student.